Réponses

2014-05-27T23:09:45+02:00
Bonsoir,

\dfrac{10x^3-20x^2+5bx^2-10bx}{2x^4-x^3-6x^2}

Factorisons le numérateur.

10x^3-20x^2+5bx^2-10bx=5x(2x^2-4x+bx-2b)\\=5x[(2x^2-4x)+(bx-2b)]\\=5x[2x(x-2)+b(b-2)]\\=5x(x-2)(2x+b)

Factorisons le dénominateur.

2x^4-x^3-6x^2=x^2(2x^2-x-6)\\=x^2(2x^2-4x+3x-6)\\=x^2[(2x^2-4x)+(3x-6)]\\=x^2[2x(x-2)+3(x-2)]\\=x^2(x-2)(2x+3)

D'où 

\dfrac{10x^3-20x^2+5bx^2-10bx}{2x^4-x^3-6x^2}\\\\=\dfrac{5x(x-2)(2x+b)}{x^2(x-2)(2x+3)}\\\\=\dfrac{5(2x+b)}{x(2x+3)}

Par conséquent, 

\boxed{\dfrac{10x^3-20x^2+5bx^2-10bx}{2x^4-x^3-6x^2}=\dfrac{5(2x+b)}{x(2x+3)}}